2022
DOI: 10.3390/polym14112227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Nanoparticles as Edible Coating on the Storability and Quality of Apricot Fruits

Abstract: Apricots are a fragile fruit that rots quickly after harvest. Therefore, they have a short shelf-life. The purpose of this work is to determine the effect of coatings containing chitosan (CH) as well as its nanoparticles (CHNPs) as thin films on the quality and shelf-life of apricots stored at room (25 ± 3 °C) and cold (5 ± 1 °C) temperatures. The physical, chemical, and sensorial changes that occurred during storage were assessed, and the shelf-life was estimated. Transmission electron microscopy was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Chitosan can lessen the severity of disease, possibly by enhancing PAL and PPO activity, lignification brought on by increased biosynthesis of phenolic compounds or induced secondary metabolites, and SAR ( Uthairatanakij et al., 2007 ). The loss of fruit firmness of the CNPs-treated fruits was delayed, signifying that Valencia orange fruit ripening was delayed, resulting in firmer fruit ( Algarni et al., 2022 ). According to ( Jin et al., 2018 ), the amount of insoluble protopectin degraded to simple pectin increased with the development of the storage period.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan can lessen the severity of disease, possibly by enhancing PAL and PPO activity, lignification brought on by increased biosynthesis of phenolic compounds or induced secondary metabolites, and SAR ( Uthairatanakij et al., 2007 ). The loss of fruit firmness of the CNPs-treated fruits was delayed, signifying that Valencia orange fruit ripening was delayed, resulting in firmer fruit ( Algarni et al., 2022 ). According to ( Jin et al., 2018 ), the amount of insoluble protopectin degraded to simple pectin increased with the development of the storage period.…”
Section: Discussionmentioning
confidence: 99%
“…Wantat et al (2022) reported that the application of chitosan-montmorillonite NPs in bananas delayed changes in firmness and reduced electrolyte leakage (Figure 2c). In apricots, CHNPs retained weight, total soluble contents, and total acidity (Algarni et al, 2022). Lustriane et al (2018) indicated that CHNPs delayed changes in starch content, weight, pulp-to-peel ratio, and surface morphology in bananas, while Ghosh et al (2021) applied CHNPs with silk nanodisk shape, which delayed changes in weight, firmness, color, and optical properties in the same fruit.…”
Section: Effects On Postharvest Quality and Nutritional Valuementioning
confidence: 98%
“…CHNPs with different sizes and characteristics have been studied throughout the following reports. Some CHNPs have been used to prepare emulsions to coat postharvest products (Algarni et al., 2022; Gardesh et al., 2016), while in other cases, the CHNPs have been fixed in films of different materials, such as chitosan (Allanigue et al., 2017; Wantat et al., 2022), hydroxypropyl methylcellulose (Priya et al., 2014), chitosan–surfactant (Mustafa et al., 2013), quinoa protein–chitosan (Medina et al., 2019), chitosan/polyvinyl alcohol (Ventura‐Aguilar et al., 2021), chitosan/polyvinylpyrrolidone (Ventura‐Aguilar et al., 2021), and starch (Shapi'i et al., 2020). The effects produced by CHNPs involved extended postharvest shelf life, enhanced antioxidant capacity, and delayed senescence symptoms.…”
Section: Characteristics Of Chnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apricot harvesting at their young age could lead us towards to preserve the fruit for long time. Currently, the techniques including edible coating have been using to preserve fruits and vegetables throughout the world (Algarni et al, 2022).…”
Section: Muhammad Kefayatullah* and Said Wahabmentioning
confidence: 99%